Interdisciplinary Teaching About Refugee and Migrant Policy and Experiences Using Simulation and Story (Teaching and Learning Inquiry, 2025)
This research assesses how interdisciplinary pedagogical interventions can prepare students to tackle complex problems, such as the refugee and migrant crisis. The co-authors created a six-week interdisciplinary module, introducing students to refugee and migrant rights, experiences, and challenges from two disciplinary pedagogical and substantive perspectives: international relations and literature. Students examined the refugee and migrant crisis from a macro level, engaging in a Council on Foreign Relations (CFR) simulation where they collaborated to create border policies. They then examined the issue from an individual level via refugee narratives, including participation in Narrative 4 story exchanges. Finally, they revised their policies according to what they learned. The impact of these pedagogical interventions was assessed through qualitative and quantitative analysis of student surveys, written products, and co-instructor observations. This data reveals the effectiveness of an interdisciplinary approach with regards to increased empathy, problem-solving strategies, and collaboration when teaching about complex issues like the refugee and migrant crisis. Using simulation and narrative teaching pedagogies to teach about migration and refugee issues and rights allows students the space to express their ideas, learn and understand the complexities of the issues, develop empathy, and challenge their own worldviews.Photo credit: A. Espriella, 2021